Analisis Perbandingan Metode AHP dan TOPSIS Dalam Pemilihan Asisten Laboratorium di FKOM UNIKU - maesyaroh, siti (FKOM UNIKU, 2020)
Laboratory assistant selection system is an application that is used to determine students who are eligible to become laboratory assistants based on the results of testing that has been done. The tests include a filing test (document requirements and a minimum grade of practicum and IPK courses), an interview test, micro teaching and a written test (competency). In this system can be used with several methods as comparative analysis material. This study compares two methods of decision support systems namely Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). Comparison of the two methods is based on four criteria, namely the value of interviews, written tests, academic grades, and microteaching. In this study obtained different results from each method so that it can find out which method can provide optimal results for the decision support system for the selection of laboratory assistants in the Faculty of Computer Science, Kuningan University.Keywords: Decision Support System (SPK), Analytical Hierarchy Process (AHP), Technique For Order Preference by Similarity to Ideal Solution (TOPSIS).